RELATIONSHIP BETWEEN GEOLOGIC PARENT MATERIAL AND GROWTH OF FOREST TREES IN THE GOLHISAR BASIN IN SW ANATOLIA, TURKEY - Altunbas, S.; Atalay, I; Siler, M. (Corvinus Univ Budapest, 2019)
Golhisar Basin which is located in the southern part of Lakes Region, in SW of Turkey contains four main geologic parent materials composed of serpentine-peridotite, Mesozoic limestone, Neogene marl deposit and Quaternary colluvial deposit on which Calabrian pine (Pinus brutia) and Anatolian black pine (Pinus nigra subsp. pallasiana) grow. Tree productivity and/or growth rate is considerably different on these parent materials. This is mainly related to the weathering degree of serpentine-peridotite, stratification and compactness of marl deposit and the crack structure of limestone. For example, the productive Calabrian pine (Pinus brutia) trees grow on the deeply weathered serpentineperidotite parent material in the Golhisar basin. Draft appearances of Calabrian pines are found on exposed peridotite-serpentine in sloping areas. Besides, tree biomass is low on compact marl deposit due to the fact that taproot development of trees is mostly prevented by the compact marl deposit and horizontal marl layers. The productivity of Calabrian pine and black pine (Pinus brutia) trees on the limestone is higher than on the marl deposit and low weathered serpentine in the study area, in general. The aim of this study is to illustrate the importance of parent materials containing serpentine-peridotite, limestone, marl and colluvial deposits on the growth of Pinus brutia and Pinus nigra trees in the Golhisar Basin
Keywords: tree growth; serpentine weathering; biome classification